Nepal : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that the earthquakes in April and May and protests and trade disruptions following the promulgation of a new constitution in September have exacerbated the macroeconomic policy challenges facing the Nepalese economy. Real GDP growth is estimated to have decelerated to 3.4 percent in 2014/15 (mid-July 2014 to mid-July 2015) from 5.5 percent in 2013/14. Growth is expected to gradually rebound to about 5.5 percent by 2016/17, as economic activity recovers from the earthquake and reconstruction gains momentum. Inflation is projected to rise to about 8.5 percent over the next 12 months. The medium-term outlook depends importantly on the authorities' reform efforts.